Meta Analysis: Peer Influence on Smoking Behavior in Adolescents - Asri Wahyu Azzahro; Anse Putra; Isna Nur Rohmah (Journal of Health Promotion and Behavior, 2022)
Background: Tobacco smoking is a direct cause of morbidity and mortality worldwide. Five million people die from smoking-related diseases every year in the world. If there is no change, then in the next 3 to 40 years the number of deaths and disabilities due to smoking will increase. This study aims to determine the magnitude of the influence of peers on smoking behavior in adolescents, with a primary study conducted by previous authors.Subjects and Method: This study uses a systematic review and meta-analysis with PICO, population: adolescents. Intervention: having smoking friends. Comparison: has no smoking friends. Outcome: smoking habit. The articles used were obtained from several databases, namely Google Scholar, Pubmed, SpingerLink and Science Direct from 2014 to 2020. The search keywords for the article were “smoking behavior OR “smoking activity” AND “adolescent” AND “friend smoking status”. The inclusion criteria for research articles were full-text articles using a cross-sectional study design. The subjects of the study were adolescents and the results of the study were smoking habits. Multivariate analysis with Adjusted Odds Ratio (aOR) to measure the estimated effect. Data were analyzed using the Review Manager application (RevMan 5.3).Results: A total of 9 articles with a total sample of 101,436 people, articles from Bangladesh, Sweden, Malaysia, Korea, Taiwan, Ethiopia, USA, Indonesia, and India, with selected cross-sectional studies for this systematic review and meta-analysis, Adolescents who have smoking friends are at risk of having smoking habits 13.74 times compared to adolescents who do not have smoking friends (OR= 13.74; 95% CI= 5.13 to 36.78; p< 0.001).Conclusion: Having smoking friends can increase the risk of smoking in adolescents.Keywords: peer, smoking, adolescents, behaviorCorrespondence:Asri Wahyu Azzahro. Faculty of Medicine, Universitas Muhammadiyah Surakarta. Jl. Garuda Mas, Kampus 4 UMS, Gonilan, Kartasura, Surakarta 57102, Central Java, Indonesia. Email: asriwahyuazzahro@gmail.com. Mobile: 081328543318.Journal of Health Promotion and Behavior (2022), 07(02): 152-160DOI: https://doi.org/10.26911/thejhpb.2021.07.02.07